KNOWLEDGE AND USE OF THE CONTRACEPTIVE METHODS AND THEIR RELATIONSHIP WITH THE PREVENTION OF ILLNESSES OF SEXUAL TRANSMISSION IN YOUNG - Santín Vilariño, Carmen; Torrico Linares, Esperanza; López López, María José; Revilla Delgado, Consuelo (Anales de Psicología / Annals of Psychology, 2003)
The objective of the present investigation is to describe the frequency and distribution of behaviors, attitudes and knowledge about the contraceptive methods and its relationship with behaviors of risk of transmission of illnesses. For it was evaluated it a sample constituted by 483 youths of different escolarización levels, with ages understood between 14 and 20 years, to those that a questionnaire was administered that it picks up information about its level of knowledge it has more than enough contraception, its attitudes toward the use of these methods and possible behaviors of risk. The results show the necessity to carry out a more rigorous formative action in all the age levels with the purpose of counteracting the distorted information or incomplete that they receive it of the most immediate environment.